If you built a sandbox: How children, network diversity, and community interventions are related to Google Fiber signup in disadvantaged urban communities. (July 2021) - Chen, Wenhong; Li, Xiaoqian; Huang, Gejun; Straubhaar, Joseph
Highlights: Limited scholarly work has assessed Google Fiber adoption or impact. This study examines Google Fiber signup in disadvantaged communities. A household survey shows community intervention as the most important contributor. Internet use, network diversity, expectations, and children increased signing up too. Implications include community interventions coordinating public and private efforts. Abstract: A decade after Google Fiber promised faster, cheaper internet connections in selected American cities, few studies have investigated its adoption, let alone in disadvantaged urban communities. Drawing on a household survey of public housing communities in Austin, Texas, a major Google Fiber city, we examine how relational, technological and community factors affect Google Fiber signup. Results show that community intervention combining digital inclusion programs and promotional neighborhood events was the most important contributor that elevated the likelihood of signing up for Google Fiber. Internet use, network diversity, expectations about the outcomes of digital inclusion programs, and having young children living in the household also significantly increased the likelihood of Google Fiber signing up. The findings have policy implications, highlighting the importance of coordinated efforts of the public, private, and non-profit sectors to engage underprivileged urban residents in a digital future through targeted community interventions.